ANALISIS SIFAT TANAH SEBAGAI DASAR PENGELOLAAN PERTANIAN BERKELANJUTAN DI WILAYAH GUNUNGKIDUL - Widyatama, Adiprasetya; Pambayun, Lintang Panjali Siwi; Kusumawati, Anna (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
This study aimed to assess the physical and chemical characteristics of soil at four different locations in Gunungkidul Regency, Yogyakarta Special Region, which are representative areas of dryland agroecosystems. The study locations included Sumberejo (Karangmojo), Bandung (Playen), Pringombo (Rongkop), and Gading (Playen). Parameters observed included moisture content, soil pH, soil consistency (dry and wet), specific gravity, organic matter content, and soil texture. The analysis results showed that the highest moisture content was found at Location 3 (8.30%), while the lowest was at Location 1 (6.25%). The soil pH ranged from 6.4–8.1, indicating a soil acidity level ranging from neutral to slightly alkaline. Soil consistency varied from slightly hard to very hard, and from sticky to very sticky under wet conditions. All locations had very high organic matter content, indicating good soil fertility potential. The soil texture was dominated by silt loam, which has a high water and nutrient storage capacity but requires proper aeration management. The results of this study are expected to form the basis for a strategy for sustainable dry land management in the Gunungkidul region.